Secagem e armazenamento do café: aspectos qualitativos e sanitários - Reinato, Carlos Henrique Rodrigues (2006)
The present work aimed to study both quality and sanity during drying and storage of the parchment, floater, cherry and mixture coffees submitted to the natural drying on grounds with three different sorts of floors and two distinct drying layers. The experimental design of the drying step, was made up of a completely randomized design with the treatments arranged in a factorial scheme 4 x 3 x 2, being four ways of coffee processing (mixture coffee, parchment coffee, cherry and unripe and floater), three sorts of grounds (earthen, concrete and asphalt byproduct) and two thickenings of coffee drying layer (thin and thick), amounting to 24 treatments. Two replicates per each treatment were utilized, amounting to 48 experimental units. About 15000 liters of coffee were harvested on the cloth and dried on the different grounds. Out of this total, 2400 liters were led directly to the grounds for drying (mixture coffee). About 4800 liters were washed and separated by density difference. The portion floater and the portion cherry and unripe were dried separately on the grounds. Finally, 9600 liters of coffee were washed, husked and dried on the grounds. On the grounds, the coffees were arranged in the grounds into two layers, thin (layer of one bean to the parchment coffee and 3 cm to the other coffees) and thick (4 cm to the parchment coffee and 8 cm to the other kinds of coffee). After drying, coffee samples were collected, processed and submitted to the analyses. In the storage step, the coffee coming from the several treatments was packed in jute bags and put into a wooden box situated inside a storehouse with coffee. The treatments were stored for one year and three samplings being performed, the first sampling was accomplished in the fourth month, the second in the eighth month and the last sampling in the twelfth month of storage. For evaluation of quality, the following analyses were accomplished.potassium leaching, electrical conductivity, phenolic compounds, total titrable acidity, total sugars, reducing and non-reducing sugars, cup test and counts of defects black, green, bitter and black green. To evaluate the occurrence of fungi, 25 beans without surface disinfection of each treatment were placed on Petri dish. The culture medium utilized was DG 18 (18% Dichloram Dextrose-Glucose). The incubation period was of seven days at 25C to the exteriorization and development of fungi. The observations concerning contaminated beans were performed with the naked eye, and in the cases of doubt, with the aid of the stereoscopic microscope. The fungus occurrence index was expressed in percentage. The dada were surveyed using multivariate and univariate analysis. The programs used were Multtab 4.0, Sisvar and SAS. The results obtained were organized into 3 papers. Papers 1 and 2 are concerned with the study of the chemical alterations and occurrence of fungi of the coffees submitted to two layers and on grounds with three different sorts of floors (earthen, asphalt byproduct and concrete). In paper 3, the chemical alterations occurred during storage were investigated. It was found in paper 1 that the sort of coffee and layer thickness are preponderant factors for the differentiation of the chemical and physicochemical characteristics among the coffees studied. In paper 2 the results pointed out that ground drying conducted into thick layer provided less occurrence of fungi of the genus Clodosporium and greater occurrence of fungi of the genus Fusarium, Eurotium and of the Sections Nigri and Circundati. In paper 3, the results indicated that among the factors studied drying in thick layer is the one which influence the most the loss of quality during storage.